Istirātījiyyah Ta‘līm al-Aqrān li Tarqiyati Mahārat al-Kalām Ladā Ṭullāb al-Ṣaff al-Thāmin - Imam Saukani; Salamuddin (CV. Creative Tugu Pena, 2026)
Arabic plays a vital role as a means of communication and as a medium for understanding Islamic teachings. However, many students in Islamic boarding schools continue to experience difficulties in developing Arabic speaking skills due to low self-confidence, fear of making mistakes, shyness, and teacher-centered instructional practices. This study aims to describe the planning, implementation, and outcomes of the peer tutoring strategy in improving the Arabic speaking skills of eighth-grade students at Darul Iman Islamic Boarding School, Kutacane, Southeast Aceh. This study employed a descriptive qualitative approach with a field research design involving one Arabic language teacher and 25 students of class VIII-A. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the peer tutoring strategy created a more interactive learning environment, increased students’ opportunities to practice speaking Arabic, enhanced their self-confidence, and encouraged more active participation in classroom communication. It can be concluded that peer tutoring is an effective strategy for improving students’ Arabic speaking skills in Islamic boarding schools. This study contributes to the development of collaborative Arabic language learning strategies and provides practical insights for teachers in implementing student-centered instruction. Future studies are recommended to investigate the effectiveness of peer tutoring using quantitative or mixed-method approaches involving larger samples and different educational contexts.